Update on clinical evidence (Part II): A summary of the main post market studies. Issue 1 (November 2016) - Tamburino, Corrado; Capranzano, Piera; Francaviglia, Bruno; Ina Tamburino, Claudia; Longo, Giovanni; Capodanno, Davide
Abstract : Bioresorbable vascular scaffolds (BVS, Absorb, Abbott Vascular, Santa Clara, CA) received the CE mark in October 2011, and were approved by the Food and Drug Administration in July 2016. After their introduction in clinical practice a broad amount of post‐marketing clinical experience with BVS has been generated so far in Europe and outside the United States. The available BVS registries differ in many aspects, including their being single‐center or multicenter, single‐arm or controlled, sponsored or investigator‐initiated, published or presented at a large‐scale international meeting. This article provides an overview of clinical results of the main post‐marketing studies of BVS available. © 2016 Wiley Periodicals, Inc.